PRESERVATION OF MILKS WITH ADDITION OF ANTIBACTERIAL AND AROMATIC SUPPLEMENTS PRODUCED IN JAPAN - Tatik Khusniati (Universitas Gadjah Mada, 2008)
The good antibacterial and aromatic supplements produced in Japan for preservation of milks at storage was investigated. Nineteen sweet and herb materials were made juices as supplements to preserve the milks. Bacterial counts, pH, protease activities and lipase activities of supplemented milks, and antibacterial activities of supplements were detected by total plate counts, glass electrode pH meter, azocasein, modified Dole extraction and turbidity methods. Eleven of nineteen milks added 10% of honey, garlic, ginger, horseradish, “sansho”, “yuzu”, green perilla, “nira”, green tea, bamboo leaf and “yomogi” were selected as good supplemented milks based on pH of these milks closed to pH of milks, the lower bacterial counts, protease activities and lipase activities of these milks than that without supplements, at 5 days before up to 10 days after use by date (P<0.05), consumed materials and antibacterial activities of these supplements in inhibiting Pseudomonas fluorescens P. 33 in the nutrient media.